1999
DOI: 10.1046/j.1365-4362.1999.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bacterial skin infections in children compared to adults at a tertiary dermatologic center

Abstract: It is important to monitor the trends of bacterial infections and their antibiotic susceptibility as this can assist medical practitioners in their choice of antimicrobial therapy. Such monitoring will also help to detect the emergence of resistant bacterial strains and caution us to take care in the use of certain drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…In our study we were particularly interested in the incidence of contamination of cosmetic creams by Staphylococcus , which is the most common bacterial skin pathogen 10,13,14 . Impetigo, folliculitis, and boils are common types of primary skin infections that are caused by S. aureus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study we were particularly interested in the incidence of contamination of cosmetic creams by Staphylococcus , which is the most common bacterial skin pathogen 10,13,14 . Impetigo, folliculitis, and boils are common types of primary skin infections that are caused by S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Darmstadt reported a 70% incidence of skin infections (both primary and secondary) caused by S. aureus in children 17 . In a study conducted at the National Skin Center (NSK) of Singapore, Gram‐positive organisms were isolated from 71.2% of skin infections, while Gram‐negative organisms were only responsible for 28.8% of the cases studied 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The African studies that found GAS as the predominant organism plated swabs immediately [14,15] or within 2 h [16], whereas the studies finding S. aureus predominant either did not describe plating techniques [20,21] or stated that plating was performed within 3 days [19]. Finally, living conditions rather than the climate may determine the importance of S. aureus; for example, a study in Singapore, a developed nation with a tropical climate, isolated S. aureus from 72% of lesions in children and Streptococcus species from 6.5% [25]. Second, the definition of impetigo varied or was not stated, often incorporating patients with and without scabies as well as other skin conditions such as eczema, and the populations studied included community surveys, specialist dermatology clinics or a mixture.…”
Section: Epidemiology Of Group a Streptococcal Skin Infectionmentioning
confidence: 99%
“…have similarly found Staphylococcus aureus to be the major isolate. [3][4][5][6][9][10][11][12][13] Recently, Singh et al and Malik et al too have found Staphylococcus aureus to be the causative agent of pyodermas in Rajasthan. 14,15 Way back in 1968, Dillon HC reported Streptococcus to be the leading etiological agent of impetigo.…”
Section: Discussionmentioning
confidence: 99%